Design‐to‐Device Approach Affords Panchromatic Co‐Sensitized Solar Cells. Issue 5 (6th December 2018) - Cooper, Christopher B.; Beard, Edward J.; Vázquez‐Mayagoitia, Álvaro; Stan, Liliana; Stenning, Gavin B. G.; Nye, Daniel W.; Vigil, Julian A.; Tomar, Tina; Jia, Jingwen; Bodedla, Govardhana B.; Chen, Song; Gallego, Lucía; et al.
Abstract: Data‐driven materials discovery has become increasingly important in identifying materials that exhibit specific, desirable properties from a vast chemical search space. Synergic prediction and experimental validation are needed to accelerate scientific advances related to critical societal applications. A design‐to‐device study that uses high‐throughput screens with algorithmic encodings of structure–property relationships is reported to identify new materials with panchromatic optical absorption, whose photovoltaic device applications are then experimentally verified. The data‐mining methods source 9431 dye candidates, which are auto‐generated from the literature using a custom text‐mining tool. These candidates are sifted via a data‐mining workflow that is tailored to identify optimal combinations of organic dyes that have complementary optical absorption properties such that they can harvest all available sunlight when acting as co‐sensitizers for dye‐sensitized solar cells (DSSCs). Six promising dye combinations are shortlisted for device testing, whereupon one dye combination yields co‐sensitized DSSCs with power conversion efficiencies comparable to those of the high‐performance, organometallic dye, N719. These results demonstrate how data‐driven molecular engineering can accelerate materials discovery for panchromatic photovoltaic or other applications. Abstract : A design‐to‐device study, based on algorithmic encodings of structure–property relationships, is used to identify new materials with panchromatic optical absorption. 9431 dyes are mined from the literature and optimally paired together to afford co‐sensitizing dyes with complementary optical absorption properties. Promising combinations are experimentally verified in dye‐sensitized solar cells and novel methods for characterizing dye aggregation in co‐sensitized devices are presented.